IMPLEMENTASI KONSEP EDUPRENEURSHIP DI SMK NEGERI 2 PALANGKA RAYA - Cahyani, Asnat Nyalong Tasika; Mawarni, Tamara; Sindy, Putri; Sarinawati Sarinawati; Yusnani Yusnani; Triadi, Defri (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This study aims to evaluate the effectiveness of the implementation of edupreneurship through Business Center, Mini Bank, and MPLB Payment at SMK Negeri 2 Palangka Raya. Edupreneurship combines the concepts of education and entrepreneurship to instill entrepreneurial attitudes and competencies in students. With a descriptive qualitative method, this study collects data through interviews, observations, and document analysis to understand the impact of these programs on students' competence and work readiness. The results of the study show that these programs have succeeded in fostering students' entrepreneurial spirit by providing practical experiences that are relevant to the business world. The Business Center helps students understand business management, marketing, and finance. Mini Bank introduces students to good financial management, while MPLB Payment introduces the latest financial technology. The teaching factory engages students in work practices that resemble a real industrial environment, with a strategy of local industry cooperation and internship programs.